1992
DOI: 10.1055/s-0038-1648130
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Venography, the Gold Standard for the Diagnosis of Deep-Vein Thrombosis: lmprovement in Observer Agreement

Abstract: SummaryTo determine whether the Rabinov-Paulin or the long-leg venography technique should be preferred in the diagnostic management of patients with clinically suspected deep-vein thrombosis, two independent experienced radiologists blindly assessed two different series of venograms of consecutive outpatients with clinically suspected deep-vein thrombosis. Venograms were obtained from two outpatient clinics of primary referral centres. In one centre the venograms were performed according to the technique of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 15 publications
1
72
0
2
Order By: Relevance
“…41 Even when venography is performed by experienced radiologists, inadequate imaging is common; in up to 20% of venograms there is inadequate visualization of a venous segment. 13,[42][43][44][45][46] Further, venography can be diffi cult to interpret and the designation of "DVT present" or "DVT absent" is subject to a considerable degree of both intraobserver ( k values ranging from 0.56-0.95) and interobserver ( k values ranging from 0.47-0.92) variation. 43 53 of patients).…”
Section: Venography: Reference Standard For Diagnosis Of Dvtmentioning
confidence: 99%
“…41 Even when venography is performed by experienced radiologists, inadequate imaging is common; in up to 20% of venograms there is inadequate visualization of a venous segment. 13,[42][43][44][45][46] Further, venography can be diffi cult to interpret and the designation of "DVT present" or "DVT absent" is subject to a considerable degree of both intraobserver ( k values ranging from 0.56-0.95) and interobserver ( k values ranging from 0.47-0.92) variation. 43 53 of patients).…”
Section: Venography: Reference Standard For Diagnosis Of Dvtmentioning
confidence: 99%
“…It was by the use of this technique that the errors of the clini cal examination were recognized. Currently it is still regarded as the gold standard for the assess ment of the diagnosis of DVT [30]. If adequately performed, CV outlines the entire deep venous system of the leg, including the common iliac vein and inferior caval vein.…”
Section: Contrast Venographymentioning
confidence: 99%
“…The second limitation of CV is related to the sometimes difficult technique and interobserver disagreement in interpretation of the venograms [30,39,40], Lensing et a l compared the Rabinov technique [21] with the long-leg method: the in jection of a larger volume of contrast medium and the concomitant use of long films instead of spot films. They concluded that the long-leg method is superior, since it significantly improved interobserver agreement (from 79 to 96%) and increased the number of interpretable venograms (from 80 to 98%) [30].…”
Section: H Janssen Et a L / Netherlands Journal O F Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis of level 1 studies evaluating this issue estimates a sensitivity of 62% (7). If a sensitivity of 62% and an expected rate of DVT of 30-60 % (10,(12)(13)(14) are assumed, the number of DVTs anticipated in this study would be 12 to 24. The study group may also be subject to a selection bias.…”
Section: Original Researchmentioning
confidence: 99%